Special Issue: Selected Papers from the 1st International Electronic Conference on Entomology - Nickolas G. Kavallieratos (Insects, 2022)
The 1st International Electronic Conference on Entomology (1IECE) was held between 1 and 15 July 2021 on the MDPI Sciforum platform organized and funded by the international journal Insects [...]